Estudo dos processos de eletrodeposição de filmes finos de Se, ZnSe e PbS - Fernandes, Valéria Cristina (Universidade Federal de São Carlos, 2008)
This work describes studies on the underpotential deposition (UPD) of selenium, zinc, as well for Zn/Se systems deposited on polycrystalline Pt electrodes in acid solutions. The effects of Zn presence in the Se dissolution process were also investigated in the UPD and bulk potential range, 0.6 and 0.03 V respectively. The measurements were carried out using cyclic voltammetry and electrochemical quartz crystal microbalance (EQCM). Furthermore Lead sulfide (PbS) multilayers were grown on a single crystal Ag(111) substrate by Electrochemical Atomic Layer Epitaxy (ECALE) method. For Zn UPD in sulfuric acid, two different processes were observed, which are attributed to the dissolution of submonolayer of Znads and H-atoms adsorbed on the electrode surface. For Se UPD was observed that hydrogen desorption were completely inhibited indicating that Se film recovered the Pt surface. The deposition of UPD Se in perchloric acid solution showed the transference of 4 electrons with 1.4 and 1.12 active sites of Pt occupied by 1 Se ad-atom in the UPD and bulk potential range, respectively. In the evaluation of the Se monolayers dissolution process formed at 0.03 V during 2000 s a process not mentioned in the literature it was observed which was evaluated by the technique MECQ. The experimental results obtained by this technique allowed to end that the dissolution process occurred by two stages, and the first involved the participation of 6e-. The dissolution mechanism with 6e- happens with the participation of water in the dissolution process of Se, leading to the formation of an oxygenated selenium compound which in next step undergo slow oxidation and is dissolved as soluble Se(VI) species. Then the total dissolution process of Se occurs in a six-electron transfer reaction. For Se deposition in the Zn presence the dissolution charges associated with Se UPD increase, indicating that the presence of Zn favors the deposition of UPD Se. In the case of PbS multilayers on Ag (111) the voltammetric analysis of the first PbUPD and SUPD peaks indicates a mechanism of two-dimensional growth, which is consistent with epitaxial growth. Electrochemical stripping measurements indicate that the amount of Pb and S deposited in a given number of cycles is a function of the number of cycles employed, again suggesting a layer-by-layer growth. This result indicates that the amount of Pb and S in these films corresponds to the stoichiometric 1:1 ratio, indicating the formation of a compound.
Study of electrodeposition processes of Se, ZnSe and PbS thin films
Keywords: Eletrodeposição; Deposição em regime de subtensão (DRS); ZnSe; PbS; Electrochemical Atomic Layer Epitaxy (ECALE); Semicondutores; CIENCIAS EXATAS E DA TERRA::QUIMICA